Pemberdayaan UMKM Melalui Sertifikasi Halal Di Desa Tulung Kecamatan Sampung Ponorogo: Halal, Pendampingan, Sertifikasi Jaminan Halal, Sosialisasi, UMKM - Kumala Sari, Vinca; Noerfadilla, Nadya; Nindyawati, Surya Ayu; Syukroni, Azid (Jurnal Abdimas Multidisiplin, 2023)
The need for halal certification is an important requirement for MSMEs, because with the existence of halal certification, it is a halal guarantee for customers to consume it. In reality, 100% of MSME product are not yet 100% for various reasons. Some reasons is that they are unable to understand the management procedures for halal product labeling, so the is need for outreach and assistance. During the Real Work Lecture and Community Service at the University of Muhammadiyah Ponorogo this time, we carried out outreach and mentoring activities for MSMEs to arrange the issuance of halal labels for their products. This activity was carried out in Tulung Village, Sampung District with 7 MSMEs that have been Halal certified for their products, namely snacks, tempe, business, shrimp crackers, pecel sauce and wingko and will be followed by several MSMEs which are currently still the process of preparing complete documents.